MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DI MI MA’ARIF NU O3 TUNJUNGMULI PURBALINGGA - Khotibul iman (IAIN Purwokerto, 2015)
Abstract: This study was motivated by the conditions of student leaming outcomes is low, especially in mathematics. This is because the teacher in the leaming still using conventional leaming models that emphasize only cognitive aspects so that students feel math becomes difficult subjects and make students saturated. The results of this study indicate that through this TGT leaming model will provide an atmosphere of leaming and classroom dynamics to be active and also gives interest to the students so that student leaming outcomes increased because in this model there is a game. In this research will be applied a TGT model innovation. Knowledge discovered and established and developed by the students themselves creatively then constructed by the students as well. The Team Games Toumament (TGT) leaming model managed to create leaming more communicative and dynamic at the same time improve leaming outcomes in Ml Maarif NU 03 Tunjungmuli Purbalingga Keywords: Model Leaming Teams Games Toumament (TGT)